Análisis cualitativo de herramientas lean para la generación de una guía aplicable a la cadena de abastecimiento de la construcción de vivienda en Bogotá D.C. (2020)
In construction of architectural projects, the waste in processes along the supply chain is not easily controlled, because they are largely outsourced activities, and because of the variability in their execution times; as a result, projects take longer than planned to execute and this increases its costs. The objective of this study is to perform a qualitative content analysis of the different lean tools applicable to production systems, and of the current situation of Lean Construction, in order to obtain a decisive theoretical framework that allows to propose a guide for the application of these tools in the construction sector, without increasing the investment of the projects, that groups the most important approaches that are adaptable to the main actors of this supply chain, particularly in housing projects in Bogotá, and that also allow construction companies to develop their processes based on lean systems and encourage continuous improvement. This application guide is submitted to validation by different professionals in construction sector, and it will be the basis for further research studies such as the implementation and evaluation of said development or the creation of others. For the development of the research, Mayring's qualitative content analysis research method will be used as the basis.